2019
DOI: 10.1093/ehjci/jez001
|View full text |Cite
|
Sign up to set email alerts
|

Bicuspid aortic valve behaviour in elite athletes

Abstract: Aims To determine the prevalence and characteristics of bicuspid aortic valve (BAV) among elite athletes and to analyse the effect of long-term exercise training on their aortas. Methods and results Consecutive BAV and tricuspid aortic valve (TAV) elite athletes from a population of 5136 athletes evaluated at the Sports Medicine Center of the Spanish National Sports Council were identified using echocardiography. A total of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Thus, our data suggest that aortic root and ascending aorta dilation are not associated with regular physical activity in paediatric BAV patients during 2-year follow-up. The recommendations for sports eligibility for patients with BAV are consistent with the ACC/AHA valve and aorta guidelines [10,27], and should be tailored to anatomical concern and sport demands. In these subjects, the risk of SCD coming from aortic rupture or dissection is related most commonly to progressive valvular heart disease and aorta dilation [6].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Thus, our data suggest that aortic root and ascending aorta dilation are not associated with regular physical activity in paediatric BAV patients during 2-year follow-up. The recommendations for sports eligibility for patients with BAV are consistent with the ACC/AHA valve and aorta guidelines [10,27], and should be tailored to anatomical concern and sport demands. In these subjects, the risk of SCD coming from aortic rupture or dissection is related most commonly to progressive valvular heart disease and aorta dilation [6].…”
Section: Discussionmentioning
confidence: 94%
“…It is a belief that increased blood pressure and aortic wall shear stress during physical exertion may increase the risk of aneurysm formation, aortic dissection or rupture in patients with genetic syndrome associated with aortopathies [10], but the role of regular physical training in BAV patients has not been fully evaluated. Recently, Boraita et al [27] studied the prevalence and the characteristics of BAV among elite athletes to analyse the effect of long-term exercise training on their aortas. Of 5316 elite athletes, 41 subjects with BAV were identified and, among these, 16 athletes had undergone two or more cardiac evaluations to assess their clinical course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of follow‐up (mean 13 years follow‐up period), the authors observed that, in high‐risk athletes with BAV, the progression of valvular disease occurred independently from the former athletic activity and that the majority of athletes with mild BAV had a benign clinical course 52 . Furthermore, in competitive athletes with BAV, in a medium‐term follow‐up, exercise seems not to have a negative impact on left ventricle (LV) structure and function 51,53,54 . Stefani et al in a study evaluating 292 subjects with BAV (210 athletes, 23 ex‐athletes, and 59 controls) showed that there were no significant changes in LV morphology and function among the different BAV patterns in a 5‐year follow‐up 51 …”
Section: What Are the Effects Of Sports Activity In Athletes With Bav?mentioning
confidence: 99%
“…Therefore, the current evidence would suggest that BAV elite athletes with mild to moderately dilated aortas may engage in high‐dynamic cardiovascular exercise without adverse consequences, although an echocardiographic follow‐up is strongly recommended 53 …”
Section: What Are the Effects Of Sports Activity In Athletes With Bav?mentioning
confidence: 99%